Membran PVA-chitosan crosslinked untuk pemisahan campuran etanol-air secara pervaporasi - I Noezar (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2008)
One of the technologies for ethanol-water separation is pervaporation. The principles of pervaporation is based on the difference in diffusional rate and solubility of the solution components in membranes. The performance of the membrane, in terms of flux and selectivity, is influenced by the swelling of the membrane due to the interaction between the solution components and the membrane materials. Membrane modification is done by forming chemical bonding between PVA and chitosan, using glutaraldehyde as crosslinking agent. The performance of the PVA-chitosan crosslinked membrane for ethanol-water separation is characterized by high mass flux and reasonably high selectivity. Pressure observed on the permeate side was 0.5 mbar, with a feed ethanol concentration of 93%. Experimental results indicate that the PVA membrane has a higher degree of swelling compared to the crosslinked PVA-chitosan membrane. The PVA-chitosan crosslinked membrane has a higher selectivity compared to the PVA membrane. The highest flux of 0.833 kgm-2hour-1 was produced by the PVA membrane. The highest selectivity of 2.820 was obtained using a 1:1 PVA-chitosan crosslinked membrane.Keywords: PVA-chitosan; crosslinked; pervaporation Abstrak Salah satu teknologi untuk pemisahan etanol-air adalah pervaporasi. Prinsip pemisahan pervaporasi adalah dengan perbedaan laju difusi dan kelarutan komponen campuran pada membran. Kinerja membran berupa fluks dan selektivitas dipengaruhi oleh kondisi swelling membran akibat interaksi komponen dengan material membran. Modifikasi membran dilakukan dengan membentuk ikatan kimia antara PVA dan chitosan dengan glutaraldehid sebagai crosslinking agent. Kinerja membran PVA-Chitosan crosslinked dalam pemisahan campuran etanol-air berupa fluks massa yang tinggi dan selektivitas yang cukup besar. Tekanan pada sisi permeat 0,5 mbar dengan konsentrasi etanol umpan 93%. Hasil penelitian menunjukkan membran PVA memiliki nilai derajat swelling lebih tinggi (0,088) daripada membran PVA-Chitosan crosslinked. Membran PVA-Chitosan crosslinked memiliki selektivitas lebih tinggi daripada membran PVA. Fluks terbesar dimiliki oleh membran PVA senilai 0,833 kgm-2jam-1membran PVA-Chitosan crosslinked 1:1 sebesar 2.820.Kata Kunci : PVA-Chitosan; crosslinked; pervaporasi